Perancangan dan Pembuatan Website Social Commerce Marketplace dengan Memanfaatkan API Media Sosial - Ariani Kartika Suwignyo; Justinus Andjarwirawan; Henry Novianus Palit (Jurnal Infra, 2015)
Social commerce marketplace website is a website that acts as a third party to bridge transactions between buyers and sellers as well as optimizes the use of social media. With the payment gateway provided by the marketplace website, buying and selling transactions online can be done safely so a buyer does not need to hesitate if s/he wants to buy a product from a seller. Similarly, the seller also should not hesitate to sell his/her products to anyone.Utilizing the API provided by Facebook and Instagram, the marketplace website can be integrated with those social media. A Facebook user can sign up with his/her account and share products from the marketplace website to his/her social media accounts. In addition, e-commerce sellers who use Facebook or Instagram for online business can upload their products directly from those social media. Automatically, the products that had been uploaded can be viewed on the marketplace website. Thus, the e-commerce sellers can reach a wider customer base.